Beyond the Iron Throne: exploring the representation of homosexuality in the series Game of Thrones - Louis, Gerome Karthic Kumar; Chithra, Gandhapodi K. (Frontiers in Sociology, 2024)
IntroductionThis research delves into the representation of homosexuality in the television series Game of Thrones, adapted from George R.R. Martin's A Song of Ice and Fire saga. The study focuses on the navigation and portrayal of homosexual identities and relationships within a historically patriarchal and heteronormative genre.MethodologyA qualitative research approach, specifically thematic analysis, was utilized to scrutinize the portrayal of homosexuality across all eight seasons and 73 episodes of Game of Thrones. The analysis encompassed pivotal scenes, character development, and dialogues related to homosexual representation.FindingsThematic analysis revealed several significant themes concerning the representation of homosexuality, including heteronormativity, the interplay of love and war, and the societal and personal impacts of sexual identity. The series portrays the challenges and resilience of homosexual characters, such as Renly Baratheon and Loras Tyrell, against a backdrop of political intrigue and personal ambition. However, the depiction at times veers into sensationalism, which may potentially desensitize viewers to the real-life struggles faced by LGBTQ+ individuals.DiscussionThe study findings suggest that while Game of Thrones aims to depict homosexual relationships with complexity and depth, it also risks perpetuating negative stereotypes and sensationalizing trauma for dramatic effect. This dual portrayal underscores the broader challenge within popular media to balance representation with responsible storytelling. The study emphasizes the necessity for more nuanced and empathetic portrayals of marginalized groups to promote greater understanding and inclusivity in media narratives.